Toward Patient Specific Models of Pediatric IVDs: A Parametric Study of IVD Mechanical Properties - Pickering, Edmund; Pivonka, Peter; Little, J. Paige (Frontiers in Bioengineering and Biotechnology, 2021)
Patient specific finite element (FE) modelling of the paediatric spine is an important challenge which offers to revolutionise the treatment of paediatric spinal pathologies, for example adolescent idiopathic scoliosis (AIS). In particular, modelling of the intervertebral disc (IVD) is a unique challenge due to its structural and mechanical complexity. This is compounded by limited ability to non-invasively interrogate key mechanical parameters of a patient's IVD. In this work, we seek to better understand the link between mechanical properties and mechanical behaviour of patient specific FE models of the paediatric lumbar spine. A parametric study of IVD parameter was conducted, coupled with insights from current knowledge of the paediatric IVD. In particular, the combined effects of parameters was investigated. Recommendations are made towards areas of importance in patient specific FE modelling of the paediatric IVD. In particular, collagen fibre bundles of the IVD are found to dominate IVD mechanical behaviour and are thus recommended as an area of primary focus for patient specific FE models. In addition, areas requiring further experimental research are identified. This work provides a valuable building block towards the development of patient specific models of the paediatric spine.